2021
DOI: 10.1002/pros.24180
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint B7‐H3 protein expression is associated with poor outcome and androgen receptor status in prostate cancer

Abstract: Background: Novel immune checkpoint-based immunotherapies may benefit specific groups of prostate cancer patients who are resistant to other treatments. Methods:We analyzed by immunohistochemistry the expression of B7-H3, PD-L1/ B7-H1, and androgen receptor (AR) in tissue samples from 120 prostate adenocarcinoma patients treated with radical prostatectomy in Spain, and from 206 prostate adenocarcinoma patients treated with radical prostatectomy in Norway.Results: B7-H3 expression correlated positively with AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have reported higher levels of AR protein expression in patients with higher B7‐H3 protein expression 5,27 and an enrichment of AR signaling‐related gene expression signatures among those with higher B7‐H3 mRNA expression 2 . Next, we investigated whether the AR‐A score, a previously reported 9‐gene signature of AR‐A in the intermediate‐risk/high‐risk subcohort, 17 was correlated with B7‐H3 protein or mRNA expression (Table 3).…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have reported higher levels of AR protein expression in patients with higher B7‐H3 protein expression 5,27 and an enrichment of AR signaling‐related gene expression signatures among those with higher B7‐H3 mRNA expression 2 . Next, we investigated whether the AR‐A score, a previously reported 9‐gene signature of AR‐A in the intermediate‐risk/high‐risk subcohort, 17 was correlated with B7‐H3 protein or mRNA expression (Table 3).…”
Section: Resultsmentioning
confidence: 91%
“…The PCa cohort has been previously described ( 41 ). Briefly, it consisted of 120 PCa patients treated with radical prostatectomy at Cruces University Hospital (Barakaldo, Spain) between 2000 and 2005.…”
Section: Methodsmentioning
confidence: 99%
“…In cancers, B7-H3 acts as an inhibitory immune checkpoint that negatively regulates anti-tumor immunity. Overexpression of B7-H3 in tumor tissues is a poor prognostic biomarker in prostate cancer [ 29 ], upper tract urothelial carcinoma [ 30 ], small cell lung cancer [ 31 ], etc. Besides, inhibition of B7-H3 expression is a promising therapeutic strategy for human cancer.…”
Section: Discussionmentioning
confidence: 99%